Organoleptic Test Of Butter Substitution Formulation With Avocado Flesh (Persea Americana Mill) On The Thousand Layers Roll - Putri Rizkiyah; Ilham Junaid; Dewi Andriani (Politeknik Pariwisata Makassar, 2022)
The aim of this study was to describe the effect of the substitution of butter with avocado flesh on the organoleptic properties of the thousand layers roll. The second objective of this study was to describe the community's acceptance of the hedonic test on the substitution of butter with avocado flesh on a thousand layers roll. Based on the Duncan test, the entire treatment had significant differences in texture and taste. Whereas color and scent have differences in treatment F0 and F1 but have significant differences in treatment F2 and F3. This is because the texture and taste are largely determined by the level of maturity of the avocado, not all avocados can be precise and the weight ratio used between treatments. In addition, the fiber and fat in the avocado are stronger so that the more avocado content, the thicker it will be and dominate the rolled legit layer cake. In terms of quality of treatment F3 (60% butter, 40% avocado) has the highest value with color 5.68 (like category), texture (like category), scent 5.48 (somewhat like category) and taste 5.84 (like category). Of the four treatments, there was one treatment that was somewhat disliked by the panelists, namely F0 where the composition of 0% avocado butter with an inaccurate formula resulted in the finished product of rolled legit rolls, which differed greatly from the finished results of the other three treatments (F1, F2 and F3). This is because the avocado content cannot fully replace the function of butter in the thousand layers roll.